Antioxidant activity and laxative effects of tannin-enriched extract of Ecklonia cava in loperamide-induced constipation of SD rats - Kim, Ji Eun (PLoS One, 2021)
To investigate the role of tannin-enriched extracts of Ecklonia cava (TEE) on the regulation of oxidative balance and laxative activity in chronic constipation, we investigated alterations after exposure to TEE, on constipation phenotypes, muscarinic cholinergic regulation, and oxidative stress responses in the transverse colons of SD rats with loperamide (Lop)-induced constipation. This extract contains high levels of total condensed tannin content (326.5 mg/g), and exhibited high inhibitory activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals. TEE treatment induced significant improvements in reactive oxygen species (ROS) production, superoxide dismutase (SOD) expression and nuclear factor erythroid 2-related factor 2 (Nrf2) phosphorylation in primary smooth muscles of rat intestine cells (pRISMCs) and transverse colon of constipation model. Also, Lop+TEE treated groups showed alleviated outcomes for the following: most stool parameters, gastrointestinal transit, and intestine length were remarkably recovered; a similar recovery pattern was observed in the histopathological structure, mucin secretion, water channel expression and gastrointestinal hormones secretion in the transverse colon; expressions of muscarinic acetylcholine receptors M2/M3 (mAChR M2/M3) and their mediators on muscarinic cholinergic regulation were significantly recovered. Taken together, these results provide the first evidence that TEE stimulates oxidative stress modulation and muscarinic cholinergic regulation when exerting its laxative effects in chronic constipation models.